2008
DOI: 10.1097/grf.0b013e318180ba84
|View full text |Cite
|
Sign up to set email alerts
|

Role of Exercise and Nutrition in Menopause

Abstract: Menopause and the aging process itself cause many physiologic changes, which explain the increased prevalence of chronic diseases observed in postmenopausal women. Exercise and nutrition play important roles in the prevention and treatment of cardiovascular disease, cancer, obesity, diabetes, osteoporosis, and depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 77 publications
2
34
0
3
Order By: Relevance
“…Exercises can not only promote their health, but also can help to prevent psychological symptoms such as anxiety and depression 25) . Furthermore, post-menopausal women can effectively avoid osteoporosis by exercise 26) .…”
Section: Discussionmentioning
confidence: 99%
“…Exercises can not only promote their health, but also can help to prevent psychological symptoms such as anxiety and depression 25) . Furthermore, post-menopausal women can effectively avoid osteoporosis by exercise 26) .…”
Section: Discussionmentioning
confidence: 99%
“…19 Studies consider that total cholesterol and LDL-c continue to increase in women until the age of 70. 20 Gonadal failure in the post-menopausal climacteric may be related to the elevation of total cholesterol and LDL-c levels, due to a decrease in the hepatic activity of 7-α-hydroxylase, with a reduction of biliary acid synthesis and, therefore, a decrease in cholesterol excretion. 21 Galvão et al 22 found an association between triglycerides and endothelial dysfunction, suggesting that triglycerides play an important role in endothelial dysfunction: they found that elevated levels of triglycerides cause an increase in lipolysis with a consequent increase of inflammatory markers, such as ultra-sensitive C-reactive protein (us-CRP) and interleukin 6, which leads to endothelial dysfunction.…”
Section: Original Articlementioning
confidence: 99%
“…Regular physical exercise may decrease a woman's risk of developing several medical illnesses, including osteoporosis, cardiovascular disease, obesity, and depression (Hagey and Warren 2008). In addition, due to the characteristics of water, the exercises performed in the aquatic environment are safe (Meredith-Jones et al 2011;Alberton et al 2013a) and effective to improve physical fitness of women in aging process (Takeshima et al 2002;Bento et al 2012).…”
mentioning
confidence: 99%